An appraisal on participation and decision making at community development meetings at Caledonia Housing Cooperatives (February 2014) - Rusenza, Eunice (Midlands State University, 2014)
The research analyzes the interactive proceedings which took place at community meetings in a bid to develop that particular community. Anchored heavily by the appraisal theory, the research analyzed cooperative meetings conducted at Caledonia Housing cooperatives in a bid to make an appraisal of the discourse of participants during community development decision making meetings. The research is an observational research where voice recording and note taking are employed and the researcher uses these strategies so covertly so as to observe behaviours which determine trends or specific actions. The research proves that the creation of a speaker’s attitudes, feelings, important judgments or assessments offers a relationship between individual personality, societal action and culturally-situated meaning. The cooperatives meetings through the use of turn-taking and engaging of participants by the Ministry, develops the issue of participation and decision making at spoken discourses. At least seven meetings were interpreted and analyzed using conversation analysis and the appraisal theory. The main reason for the analysis of these meetings was to bring out how the interpersonal meaning is realized in utterances made by participants at community development meetings.